The Relationship between Gender and Tax Payments - Hendra Gunawan; Melisa Melisa (Pusat P2M Politeknik Negeri Batam, 2017)
Paying taxes is one deduction from earnings in a company, a few companies are working to find a way to minimize tax payments but still within reasonable limits and do not violate the rules of law that have been defined. This study aims to determine the effect of gender on tax payments using control variables ROA, size, and leverage. Measurement gender is using dummy variables. Dependent measurements are measured using the tax payments CETR. The population used in this study is all companies except for the construction sector and the financial sector. The sample was selected using purposive sampling and data obtained as many as 237 companies. The results showed that gender had no effect on the payment of taxes, while the ROA and size control variables showed a significant result which means the ROA and size affect the payment of taxes. Leverage control variables showed significant results, which means leverage does not affect the payment of taxes in a company.